Effect of date of harvest on the nutritional quality of native grass hay - Baker, J.C.; Tonn, S.R.; Kehler, David E.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Native grass hay meadows in three Kansas Flint Hills counties were sampled at 2-week intervals during the growing season to determine the effect of harvest date on forage quality. Each sample was analyzed for crude protein (CP), acid detergent fiber (ADF), and phosphorus (PHOS). CP and PHOS contents declined, and ADF increased as harvest date progressed into the growing season. Both CP and ADF were related highly to harvest date. PHOS content was associated only moderately with harvest date. Harvest date of native grass hay can significantly influence supplemental protein needs for beef cows.
Keywords: Beef; Native grass; Hay; Forage quality; Cows